The flower and the scorpion : sexuality and ritual in early Nahua culture - Sigal, Peter Herman, 1964- (Latin America otherwise., 2011)
Sigal argues that sixteenth century Nahua sexuality cannot be fully understood only through colonial sensibilities and sources. He examines legal documents, clerical texts, pictorial manuscripts, images and glyphs of Nahua gods and goddesses and descriptions of fertility rituals and other historical accounts and stories to show the complexity of Nahua sexuality.